Clarifying the concept of social capital through its three perspectives: individualistic, communitarian and macrosocial - Matiás Membiela-Pollań; JoseÁtilano Pena-Loṕez (European Journal of Government and Economics (EJGE), 2017)
The concept of social capital has received increasing attention in recent years. The complexity and multidimensionality that accompany the variable of social capital have caused confusion and ambiguity. This article presents a synthesis of social capital in three perspectives. From the individualistic or micro-social perspective, social capital is an "individual resource" that consists of the networks of relations of the focal subject that bring it a set of instrumental and expressive resources. For the communitarian or meso-social perspective, social capital is a "community resource" or set of attributes and properties present in the social structure (shared norms and values, private trust, closure ...) that facilitate its functioning and collective action. Finally, for the macrosocial perspective, social capital is a "macrosocial and macroinstitutional resource" resting on aspects such as civic-mindedness, general trust and social cohesion, which favors the functioning of the economy and society in general.
Keywords: 330; Social capital; individual social capital; communitarian perspective of social capital; general trust